Tandem Photovoltaic Cells - (:unkn) unknown (Konarka Technologies Inc., 2009)
This disclosure relates to tandem photovoltaic cells, as well as related systems, methods, and components. In one aspect, this disclosure features systems that include first and second semi-cells. The first semi-cell includes a first electrode, a third electrode, and a first photoactive layer between the first and third electrodes. The second semi-cell includes a second electrode, the third electrode, and a second photoactive layer between the second and third electrodes. The first and second semi-cells are electrically connected in parallel. The third electrode is between the first and second electrodes and includes a first material selected from the group consisting of metals, carbon nanotubes, carbon nanorods, fallerenes, and combinations thereof. The systems are configured as photovoltaic systems.
Keywords: Contact, Coating, Or Surface Geometry (136/256); Photovoltaic cells; Energy; H01L 31/00 (20060101); Electricity; Electrodes